The Presence of Aedes Aegypti Mosquito larvae in Bandung City in 2021 - Agung Sutriyawan; Karlina Wirawati; Suherdin Suherdin (Universitas Ahmad Dahlan, 2022)
Background: Dengue Hemorrhagic Fever (DHF) is the vector-borne disease with the highest prevalence rate in the world. Bandung city itself is included in the 5 regencies/cities with the highest number of cases today. The disease is transmitted through the Aedes aegypti mosquito. The purpose of this study is to find out the effect of mosquito nests on the presence of Aedes aegypti mosquitoes. Method: This research uses quantitative research methods with a design cross-sectional survey. The population in this study is the entire community in Bandung. The sample number was 510 respondents. The research instrument used questionnaires and observation sheets. Data analyzed descriptively, chi-square test, and binary logistic regression. Results: The presence of Aedes aegypti mosquitoes is influenced by several risk factors for Pemberantasan Sarang Nyamuk (PSN) behavior, including not draining water shelters once a week (OR=3.219; CI 95%= 2.194-4.724; p<0.025), not closing water reservoirs (OR=1.719; CI 95%= 1.171-2.521; p<0.025), and abate use behavior (OR=1.6; CI 95%= 1.070-2.437; p<0.025). Conclusion: In this study, most of them found no flicks in water reservoirs. The presence of Aedes aegypti mosquitoes can increase if it drains water reservoirs less than once a week, closes unsalted water reservoirs or open water shelters, does not use abate. To prevent the presence of a flick at home it is necessary to drain the water shelter regularly, always close the water shelter and sprinkle abate powder at least once every 3 months.